Intracranial hemorrhages in patients with COVID-19: a systematic review of the literature, regarding six cases in an Amazonian population - Lima, William de Sousa; Soares, Marcelo Henrique Pereira; Paschoal, Eric Homero Albuquerque; Paschoal, Joelma Karin Sagica Fernandes; Paschoal, Fernando Mendes, Jr.; Bor-Seng-Shu, Edson (Arquivos de Neuro-Psiquiatria, 2023)
Background Coronavirus disease 2019 (COVID-19) has emerged as a public health emergency worldwide, predominantly affecting the respiratory tract. However, evidence supports the involvement of extrapulmonary sites, including reports of intracranial hemorrhages.Objective To describe six original cases and review the literature on intracranial hemorrhages in patients diagnosed with COVID-19 by molecular methods.Methods A systematic literature review was performed on MEDLINE, PubMed, and NCBI electronic databases to identify eligible studies. Of the total 1,624 articles retrieved, only 53 articles met the inclusion criteria.Results The overall incidence of intracranial hemorrhage in patients hospitalized for COVID-19 was 0.26%. In this patient group, the mean age was 60 years, and the majority were male (68%) with initial respiratory symptoms (73%) and some comorbidity. Before the diagnosis of hemorrhage, 43% of patients were using anticoagulants, 47.3% at therapeutic doses. The intraparenchymal (50%) was the most affected compartment, followed by the subarachnoid (34%), intraventricular (11%), and subdural (7%). There was a predominance of lobar over non-lobar topographies. Multifocal or multicompartmental hemorrhages were described in 25% of cases. Overall mortality in the cohort studies was 44%, while around 55% of patients were discharged from hospital.Conclusion Despite the unusual association, the combination of these two diseases is associated with high rates of mortality and morbidity, as well as more severe clinicoradiological presentations. Further studies are needed to provide robust evidence on the exact pathophysiology behind the occurrence of intracranial hemorrhages after COVID-19 infection.
Keywords: COVID-19; Intracranial Hemorrhages; Cerebral Hemorrhage; Hemorrhagic Stroke